Macroeconomics as determinants of stock market return in Malaysia / Mohd Amierul Hafiez Ali Abas - Ali Abas, Mohd Amierul Hafiez (2016)
This study conducted to examines the relationship between macroeconomic variables and stock market return in Malaysia. This study determined the response of stock market return which is in FTSE Bursa Malaysia Kuala Lumpur Composite Index (FBM KLCI) to shock in each of macroeconomic variables selected for this study which are the exchange rate, inflation rate and interest rate. Monthly data was set for this study from January 2006 until December 2015 which consist 120 observations for each variables. Besides that, this study will employs Ordinary least Square (OLS) to determine the statistical relationship. Based on the results of Ordinary Least Method found that depreciation of exchange rate has a negative relationship with dependant variable. In addition the remaining independent variables also found same relationship with as negative insignificant towards stock return in Malaysia.